The Bumiputera Policy: Chinese Views and Perspectives - Lee Kam Hing (Kajian Malaysia, 2003)
This paper takes the statements of various Chinese leaders and Chinesebased organizations to arrive at some general understanding of how the community responded to the bumiputera policy of the state. Of the Chinese and Chinese-based political parties, the paper considers the stand of the Malaysian Chinese Association (MCA) and Parti Gerakan Rakyat Malaysia, both being in the ruling coalition, and the opposition Democratic Action Party (DAP) especially over the New Economic Policy (NEP), introduced inl97l which carried much of the aspirations of the bumiputera policy. It also refers to the position of the nonpolitical organizations. Of these, the most important is the Associated chinese business community and the Suqiu whose statement just before the 1999 general elections was endorsed by over 2,000 of the Chinese associations in the country. It looks also at the political views of Tan Cheng Lock and Lim Lian Geok who articulated early Chinese position in a period of transition to an independent nation. In all, the individuals and the organizations represent a fair cross-section of the Chinese community.